Situation Based Learning with Peer Tutors Design in Mathematics Learning - Amalliyah, Nor; Waluya, Budi; Agoestanto, Arief (FKIP Universitas Lampung, 2022)
This study aims to determine student responses to the application of the situation based learning model with peer tutors. The method used in this research is descriptive qualitative method, with data sources consisting of primary data sources and secondary data. The research subjects consisted of 29 students. The research instrument was in the form of observation sheets and student response questionnaires consisting of 4 indicators containing 20 statements. The data analysis technique was carried out through the stages of data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was found that the application of the situation based learning model with peer tutors was carried out very well and overall received a positive response from students. Students gave positive responses to indicators of interest in mathematics, interest in learning mathematics using a situation based learning model with peer tutors, and the benefits of participating in mathematics learning using a situation based learning model with peer tutors. A very positive response was given by students on the indicators of the benefits of mathematics lessons.Keywords: students’ response, situation based learning, peer tutor. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1205-1213